2009
DOI: 10.1002/ppap.200931105
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Deposition of Adhesion Promotion Layers on Aluminium

Abstract: The paper presents investigations on the deposition of plasma polymerised films at atmospheric pressure as a pretreatment for painting and adhesive bonding of aircraft aluminium structures. Two different plasma jet sources are employed, one based on a controlled arc discharge and air as process gas, and another based on a dielectric barrier discharge (DBD) and He as plasma gas. The organosilicon precursors HMDSO, TEOS and OMCTS are used with both plasma sources. Deposition in the arc discharge plasma jet leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…The process allows for the continuous treatment and feed-through of the CNTs and is therefore ideally suited for the in-line combination with the industrial CVD -synthesis of MWCNTs. Previously this plasma source has been studied for pretreatment and coating of polymers and metals and for the oxidation of carbon fibers [16][17][18][19][20][21][22]. The objective of this study is to achieve an efficient CNT functionalization without significantly damaging the CNT structure.…”
Section: Introductionmentioning
confidence: 98%
“…The process allows for the continuous treatment and feed-through of the CNTs and is therefore ideally suited for the in-line combination with the industrial CVD -synthesis of MWCNTs. Previously this plasma source has been studied for pretreatment and coating of polymers and metals and for the oxidation of carbon fibers [16][17][18][19][20][21][22]. The objective of this study is to achieve an efficient CNT functionalization without significantly damaging the CNT structure.…”
Section: Introductionmentioning
confidence: 98%
“…A number of authors have previously described the operation of this atmospheric pressure plasma jet (APPJ) source [13][14][15][16][17]. A schematic diagram of the system is given in Figure 1, this illustrates how the blown arc is formed inside the arc cavity and ionized gas is expelled through the anode-nozzle [22 and 23].…”
Section: Equipment and Materialsmentioning
confidence: 99%
“…Amongst the plasma activation studies reported to-date with this source are those that aim to enhance the surface energy of polyethylene prior to adhesive bonding [13], adhesion improvement [6] and textile polymer treatments [14]. This source has also been used in the deposition of plasma polymerized coatings for gas barrier applications [15] and corrosion protection [16,17]. These papers have mainly focused on the process outcome as a function of anode-nozzle speeds relative to the treated surface.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the PlasmaStreamÔ system, the glow discharge Sur-Fx source, which operates at 13.56 MHz, is only used for the activation of surfaces. Figure 6 also shows a photograph of an example of an air plasma system (OpenAir system) manufactured by PlasmaTreatÔ (17)(18)(19)(20)(21)(22). The PlasmaTreatÔ is a blown arc source where dry compressed air at a pressure 100 and 300 kPa is forced through a 4-mm-diameter nozzle to form the air plasma jet.…”
Section: Industrial Examples Of Atmospheric Plasma Processing Equipmentmentioning
confidence: 99%